2014
DOI: 10.1007/s10040-014-1210-5
|View full text |Cite
|
Sign up to set email alerts
|

The soil–water flow system beneath a cotton field in arid north-west China, serviced by mulched drip irrigation using brackish water

Abstract: A field experiment was carried out in southern Xinjiang, China, to reveal soil-water flow pattern beneath a combined plastic-mulch (film) and drip-irrigation system using brackish water. The soil-water flow system (SWFS) was characterized from soil surface to the water table based on observed spatio-temporal distribution of total soil-water potential, water content and electric conductivity. Root suction provided a strong inner sink. The results indicated that SWFS determined the soil salinity and moisture dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 42 publications
(56 reference statements)
1
28
0
Order By: Relevance
“…Due to the soil structure of loam and the shallow groundwater table, there were two obvious fluctuations during the two irrigation periods in this study, as shown in Fig. 3, and the downward water flow from irrigation water below the divergent surface of zero flux arrived at the water table soon after the irrigation events (Li et al, 2015). Taking an irrigation period for example, the water table was lower at the beginning of irrigation, but began to respond and rise some hours after the end of the irrigation event.…”
Section: Water-table Fluctuation Methods (Wtf)mentioning
confidence: 83%
See 2 more Smart Citations
“…Due to the soil structure of loam and the shallow groundwater table, there were two obvious fluctuations during the two irrigation periods in this study, as shown in Fig. 3, and the downward water flow from irrigation water below the divergent surface of zero flux arrived at the water table soon after the irrigation events (Li et al, 2015). Taking an irrigation period for example, the water table was lower at the beginning of irrigation, but began to respond and rise some hours after the end of the irrigation event.…”
Section: Water-table Fluctuation Methods (Wtf)mentioning
confidence: 83%
“…The land surface elevation is about 901 m above the mean sea level (Li et al, 2015). It is classified as a continental desert climate with an average annual precipitation of only 58 mm and maximum potential evaporation of 2788.2 mm.…”
Section: / 46mentioning
confidence: 99%
See 1 more Smart Citation
“…The altitude is between 895 m and 903 m. The climate in the study area belongs to warm temperate continental desert climate. Soil texture is loamy sand soil with lower soil fertility [8]. …”
Section: Study Areamentioning
confidence: 99%
“…N utrient element transport through the ecosystem is a critical component of global biogeochemical cycles. In arid or semiarid areas, brackish water is used for irrigation because of a lack of fresh water (Li et al, 2015). Salt‐tolerant plants such as cotton, which can withstand relatively high salt stress, are the preferred crops in such regions.…”
mentioning
confidence: 99%